APPLICATION OF REMOTE SENSING AND GEOGRAPHICAL INFORMATION SYSTEM FOR FOREST RESOURCES BALANCE MAPPINGIN THE TARUSAN SUB-DAS, PESISIR SELATAN DISTRICT - Rizik Fadel Muhammad Hasan; Dilla Angraina (Remote Sensing Technology Study Program, 2020)
This forest resource balance mapping aims to (1) determine changes in the area of ​​forest resources in the XI Tarusan sub-district, Pesisir Selatan Regency; (2) find out the forest balance in XI Tarusan District, Pesisir Selatan District; (3) determine the accuracy of Landsat 8 imagery for preparing forest resource balances. The method used in mapping the balance of forest resources is by carrying out a supervised classification for land use and land cover. Then the data is overlaid using a two-dimensional matrix approach. Furthermore, the data is analyzed using a Geographic Information System which provides spatial information to be able to present data in map form. The results of this study are changes in the area of ​​forest resources in XI Tarusan District, Pesisir Selatan District, which is 28.62 Ha.,and the accuracy of the Landsat 8 image obtained in the preparation of this forest resource is 91.66%.